How does priority setting for resource allocation happen in commissioning dental services in a nationally led, regionally delivered system: a qualitative study using semistructured interviews with NHS England dental commissioners. Issue 3 (23rd March 2019) - Vernazza, Christopher Robert; Taylor, Greig; Donaldson, Cam; Gray, Joanne; Holmes, Richard; Carr, Katherine; Exley, Catherine
Abstract : Objectives: To understand approaches to priority setting for healthcare service resource allocation at an operational level in a nationally commissioned but regionally delivered service. Design: Qualitative study using semistructured interviews and a Framework analysis. Setting: National Health Service dentistry commissioning teams within subregional offices in England. Participants: All 31 individuals holding the relevant role (dental lead commissioner in subregional offices) were approached directly and from this 14 participants were recruited, with 12 interviews completed. Both male and female genders and all regions were represented in the final sample. Results: Three major themes arose. First, 'Methods of priority setting and barriers to explicit approaches' was a common theme, specifically identifying the main methods as: perpetuating historical allocations, pressure from politicians and clinicians and use of needs assessments while barriers were time and skill deficits, a lack of national guidance and an inflexible contracting arrangements stopping resource allocation. Second, 'Relationships with key stakeholders and advisors' were discussed, showing the important nature of relationships with clinical advisors but variation in the quality of these relationships was noted. Finally, 'Tensions between national and local responsibilities' were illustrated, where there was confusion about where power and autonomy lay. Conclusions: Commissioners recognised a need for resource allocation but relied on clinical advice and needs assessment in order to set priorities. More explicit priority setting was prevented by structure of the commissioning system and standard national contracts with providers. Further research is required to embed and simplify adoption of tools to aid priority setting.